Sokongan sosial rakan sebaya sebagai sumber kesejahteraan subjektif: kajian dalam kalangan remaja sekolah menengah di Yogyakarta, Indonesia - Gusniarti, Uly,; Jaafar, Jas Laile,; Hutagalung, Fonny D., (Penerbit Universiti Kebangsaan Malaysia, 2023)
A great number of studies have consistently reported that peer social support escalates subjective well-being. As studies on both aspects are limited in Indonesia, and acknowledging the Eastern culture-specific role the peers bring to the social development of the teenagers, the present study attempts to determine the relationship between peer social support and subjective well-being among secondary school teenagers in Yogyakarta, Indonesia. A total of 267 adolescents (148 girls, 119 boys, grade 7-9) filled out the Indonesian versions of the classmate support subscales from The Child and Adolescent Social Support Scale (Malecki, Demaray, & Elliott, 2000) and The Brief Adolescents Subjective Well-Being in School Scale (Tian, Wang, & Huebner, 2014). The results revealed that Grade 7 are found to be higher in subjective well being as compared to Grade 9 teenagers. Peer social support correlated significantly with subjective well-being and no significant gender differences are found. Overall, the results indicate that developmental differences exist but interestingly, the correlation magnitude between peer social support and subjective wellbeing is high. This could probably reflect the stronger social role of peers among collectivistic societies and indeed worth to be examined further.